Spinal Tuberculosis: Decompression and Stabilization by single posterior approach: A Multi-Centric Cohort study (Journal of Pakistan Orthopaedic Association, 2018)
Objective: To determine functional and fusion outcomes of postero-lateral decompression in spinal tuberculosis.Methods: This multi-centric study was done from January 2014 to December 2017. We included 52 patients with spinal tuberculosis spondylitis between 15 to 60 years of age of both genders diagnosed on history, routine investigation and magnetic resonance imaging (MRI). All patients were operated via posterior approach under C-arm. We stabilized the involved vertebrae with pedicle screws involving one motion segments above and below. Tuberculosis abscess was drained and decompression of the spinal cord was done. All patient’s fusion and functional outcome was assessed using Oswesrty Disability Index. We followed patient post-operative 2 weeks, 6 weeks, 12 weeks, 6 months and 1 year.Results: Amongst the total 52 patients, there were 36 (69.2%) male and 16 (32.8%) female. Mean age of the patients was 24.615±12.281 with maximum patients between 16 to 30 years of age. There were 19 (36.4%) cases of lumbar spine, 16 (30.7%) dorsal spine and 17 (32.9%) dorso-lumbar spine. Mean surgical time from start of time till closure was 101.8654±16.88.There was improvement in Oswestry disability index post-operatively, and out of total 51 patients 43 (84.31%) had no disability and only 06 (11.76%) had moderate disability and 02 (3.9%) has sever disability.Conclusion: Posterolateral decompression in patients with spinal tuberculosis has good functional and fusion outcome.